Política ambiental discrecional y bienestar social: Un modelo de inconsistencia dinámica - Leonardo J. Maldonado (Atlantic Review of Economics, 2012)
– This article evaluates the presence of dynamic inconsistency on decisions of discretionary environmental policy, and its incidence on social welfare. It is assumed that an environmental authority minimizes a social welfare loss function controlling freely - on each period - a tax rate by unit of contaminant product in its objective of reduce the quote of industrial production and increase the welfare. In a scenario of rational expectations on the tax rate is confirmed the occurrence of an instrumental bias that separated the optimal results from the social desires. In addition, with a positive exogenous and stochastic shock on the stability of policy decisions - some kind of favorable and unexpected news - the tax burden will be reduced and the industrial supply becomes promoted. At that moment, if the optimum tax rate is lower than the demanding social tax rate, there will be pollution beyond the socially tolerable. To eliminate the bias, it will be necessary to reach a cooperative solution where the environmental authority adopts the commitment to apply an optimum policy on each period, with a long-term vision, and where the society form its expectations in accord with the commitment.
Keywords: Q50; E61; D64; 330